The impacts of war on Russia's economic future - Iikka Korhonen; Heli Simola; Laura Solanko (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2025)
Three years of war, sanctions and Russia's isolation from the global community have changed its economy in many ways. Some changes such as the degraded business environment and increased government presence in the economy are likely to persist. War has also exacerbated Russia's already poor demographic trends. While a break in the war and relaxation of sanctions would eventually at least partially reinvigorate Russian trade with the European Union and other economic blocs, Russia's heavy dependence on China undoubtedly continues. An end to the war, even an ugly end, would reduce pressure for public sector spending and help Russia get inflation back under control. A prolonging of the war and continuation of the current sanctions regime would mean further increases in public spending as sustaining the war is non-negotiable for the current government. Inflation would remain high and economic imbalances worsen. In all our scenarios, Russia's share of the global economy continues to decline. Russia, however, has the resources it needs to continue the war, the desire to fund its armed forces and the commitment to support its military-industrial complex come what may.
urn:nbn:fi-fe2025022614526
Keywords: 330; Russia; economy; war; sanctions